Hubungan Body Image dengan Rasa Percaya Diri pada Remaja Putri yang Mengalami Perubahan Fisik Pubertas - Aliefia Salfa Priyono; Ridha Hafid; Siti Hajar Salawali (Journal of Telenursing (JOTING), 2026)
This study aims to determine the relationship between body image and self-confidence in adolescent girls experiencing physical changes during puberty at SMP Negeri 1, Gorontalo City. The method used in this study was a cross-sectional study. The results showed a significant relationship between body image and self-confidence in adolescent girls experiencing physical changes during puberty (p-value = 0.000). In conclusion, body image and self-confidence are two interrelated psychological aspects of adolescent development, particularly in girls. Girls at this age are in the process of forming body image, which is related to self-confidence. Keywords: Body Image, Physical Changes, Puberty, Self-Confidence, Adolescent Girls